ENTOMOLOGICAL SURVEY ON THE SPECIES COMPOSITION AND BEHAVIORAL CHARACTERISTICS OF MALARIA VECTORS IN KRONG NA COMMUNE, BUON DON DISTRICT, DAK LAK PROVINCE, VIET NAM - Nguyễn, Quang Thái; Hoàng, Hải Phúc; Nguyễn, Tiến Tài; Nguyễn, Hồng Nguyên; Y Bun, Toản Niê; Đỗ, Ngọc Thúy; Nguyễn, Tiến Cương; Nguyễn, Kiên Cường; Lê, Trần Khánh (Tạp chí Y học Quân sự, 2025)
Objectives: This study aimed to determine the species composition and behavioral characteristics of malaria vectors in the forest habitat of Krong Na commune, Buon Don district, Dak Lak province. Subjects and methods: A cross-sectional descriptive study was conducted in October 2023, targeting adult female Anopheles mosquitoes collected from forest habitat around border guard stations in Krong Na Commune. Results: A total of 12 Anopheles species were identified, including two primary malaria vectors—Anopheles dirus and Anopheles minimus—along with six secondary vectors. An. dirus were observed to display strong anthropophilic tendencies, biting both indoors and outdoors, while An. minimus were observed to show predominantly zoophilic behavior with occasional human biting. Both species exhibited peak biting activity between 19:00 and 21:00 and were active throughout the 18:00–24:00 period. The most dominant species were An. philippinensis (37.49%), An. minimus (32.83%), and An. maculatus (18.16%). Conclusions: It is necessary to develop adaptive and context-specific vector control strategies to mitigate malaria transmission in forested border regions.